COPEING WITH POST-TRAUMATIC STRESS IS NOT JUSTIFIED BY CRIME - Champa Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
In addition to emotions of helplessness, terror, and dread, intense sentiments of rage have the ability to emerge as a response to traumatic experiences. Indeed, irritability and outbursts of anger are listed as one of the arousal symptoms of posttraumatic stress disorder (PTSD) in the Diagnostic and Statistical Manual of Mental Disorders (4th edition, text rev., American Psychiatric Association, 2000). This definition is found in the Diagnostic and Statistical Manual of Mental Disorders. In addition, Novaco and Chemtob (1998) noted out in their review on anger and PTSD that early findings revealed anger as a prominent component of posttraumatic stress responses. This was mentioned in their discussion of how anger and PTSD are related to each other.